(untitled) (Research, Society and Development, 2021)
Salt stress is a condition that causes physiological changes in several species, the identifying cultivars tolerant to such conditions is essential to high salinity environments. The objective was to evaluate the physiological quality of seeds of chickpea cultivars to salt stress during germination and seedling growth. Two cultivars (‘BRS Cícero’ and ‘BRS Aleppo’) and five osmotic potentials simulated with sodium chloride solutions (0.0; -0.2; -0.4; -0.6 and -0.8 MPa), were evaluated by the test of germination speed index, mean germination time, epicotyl and primary root length, epicotyl and primary root fresh mass, epicotyl and the primary root dry mass of the seeds were evaluated. Significant interactions were found for all variables, indicating that there are cultivars with specific performance for a particular salt condition, and the simulated salt stress conditions negatively affected germination and seedling growth. Osmotic potentials of less than -0.4 MPa are harmful to the germination and growth of chickpea seedlings. The ‘BRS Cícero’ seeds showed a higher salt tolerance than ‘BRS Aleppo’. The cultivar BRS Aleppo has a longer epicotyl length compared to ’BRS Cícero’ when subjected to the same conditions of salt stress.